Internet of things solutions (IOTS) adoption for capital goods in the business to-business (B2B) market - BAKSHI, Amit (Institutional Knowledge at Singapore Management University, 2022)
The excitement created by the introduction of Internet of things solutions (IoTS) is yet to be converted to an all-pervasive adoption and implementation across industries for capital goods in the B2B market. Proof of concepts (POC) and pilot projects are implemented but getting to the next phase of adoption and implementation across the B2B market for capital goods, has been lacking. An exploratory mixed method is used for this research. Qualitative analysis of the semi-structured interviews with subject matter experts from users, OEMs, and service providers helped identify asset criticality, analytic intelligence, and interoperability as three core significant factors and implementation cost, vendor lock-in, and responsiveness as the interface between the core factors and adoption of IoT Solution. These factors are believed to influence the adoption of IoT Solutions, but much evidence remains conjectural or anecdotal to date. In this context, I present a systematic framework that is validated quantitatively. The causal effect of reduction in implementation costs and vendor lock-in due to interoperability and the interaction of responsiveness on the relationship between asset criticality and IoT Solutions adoption is significant. This study is expected to provide practitioners in the B2B capital goods market insight on how to increase adoption.